2022
DOI: 10.20944/preprints202203.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends of Treatment Development in Rheumatoid Arthritis: Promise, Progress, and Challenges

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, abnormal inflammatory immune response. It is characterized by the involvement of the synovium and multiple organs and the destruction of joints and articular cartilage. In the past 30 years, several promising novel compounds and antibodies have been developed for the treatment of RA. The introduction of new drugs and precision medicine for all forms of RA raises several issues related to access to novel treatments by patients, optical regimen selection, cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, existing studies on the use of Telitacicept in other autoimmune diseases have demonstrated promising results. For instance, in the treatment of systemic lupus erythematosus (SLE) ( 24 , 25 ) and rheumatoid arthritis (RA) ( 26 ), Telitacicept has shown considerable effectiveness and safety. This suggests the potential for similar results in MG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existing studies on the use of Telitacicept in other autoimmune diseases have demonstrated promising results. For instance, in the treatment of systemic lupus erythematosus (SLE) ( 24 , 25 ) and rheumatoid arthritis (RA) ( 26 ), Telitacicept has shown considerable effectiveness and safety. This suggests the potential for similar results in MG patients.…”
Section: Discussionmentioning
confidence: 99%